2016
DOI: 10.1002/ecj.11911
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Analysis of Casual Elements for Deterioration of Cylindrical EDLC

Abstract: SUMMARY Chemical analysis was carried out before and after the constant voltage hold test that was an acceleration deterioration examination to clarify deterioration factors of electric double‐layer capacitor (EDLC). The results showed that the stress test slightly caused the increase of internal resistance. It was also confirmed that the range of fluorochemicals was formed on the electrode surface for approximately 10 nm in depth using electron spectroscopy for chemical analysis (ESCA). From the chemical anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…It was also reported that aging model was calculated and aging diagnosis was built up using manufactured EDLCs under overvoltage and high-temperature condition [9][10][11][12][13][14][15][16][17][18][19][20]. For this chapter, we performed a voltage hold test, which is a type of accelerated degradation test for EDLCs using the application of overvoltage, on cylindrical EDLCs, which are used in actual applications [21]. We confirmed the degradation behaviors caused by the application of overvoltage by measuring the capacitance and internal resistance before and after the tests.…”
Section: Introductionmentioning
confidence: 99%
“…It was also reported that aging model was calculated and aging diagnosis was built up using manufactured EDLCs under overvoltage and high-temperature condition [9][10][11][12][13][14][15][16][17][18][19][20]. For this chapter, we performed a voltage hold test, which is a type of accelerated degradation test for EDLCs using the application of overvoltage, on cylindrical EDLCs, which are used in actual applications [21]. We confirmed the degradation behaviors caused by the application of overvoltage by measuring the capacitance and internal resistance before and after the tests.…”
Section: Introductionmentioning
confidence: 99%